cncتصميم وتنفيذ ماكينة - حســــــن جعفر حســـن الامــين; خـــــــالد يــــــــس حســــن محمد; محمد عبدالرحمن الرحيمة الامين (جـــامعة الـــشيخ عـــبدالله الــــــبدري, 2022)
المستخلص : تقنية التحكم الرقمي تعرف على انها التحكم فى الماكينة او عملية الانتاج عن طريق استخدام اكواد مكونة من حروف وارقام وقد بدأ ظهور هذة التقنية فى منتصف القرن العشرين وبالتحديد فى عام 1952 م حيث تم أول تطوير لتقنية التحكم الرقمي فى معهد ماسوشوست للتقنية (MIT) بالتعاون مع شركة جون بارسونس للطائرات في مدينة متشجان بالولايات المتحدة الأمريكية . ويرجع ذلك للحاجة الماسة لإنتاج قطع غاية في الدقة لأشكال هندسية معقدة تشكل أجزاء من الطائرات الحربية وخصوصا مراوح الطائرات العمودية. تكمن مشكلة البحث في انه تم تصميم ماكينة ال CNC بحيث تعمل على الرسم فقط . بدات ماكينات الCNC تغزو العالم لذا كان لابد من معرفة طرق ونظريات عملها وكيفية تصميم ماكينة CNC من المواد المحلية المتاحه وباقل تكلفه ممكنه . الهدف من البحث تصميم و تنفيذ ماكينة CNC قادرة على العمل بدقة وبسرعة عالية لزيادة كفاءة الانتاج وبالاضافة لمقارنتها ببقية الماكينات وملاحظة ادائها . تم استخدام المنهج التجريبي لتصميم وتنفيذ ماكينة ال CNC ومقارنتها مع الماكينات المعروفة في مواد التصميم من حيث التكلفة وتم استخدام لغة Arduino C لتحرير برنامج الاردوينو للتشغيل وفق النظم الحديثة . Abstract : Digital control technology is defined as controlling the machine or the production process by using codes consisting of letters and numbers. The emergence of this technology began in the middle of the twentieth century, specifically in 1952 AD, when the first development of digital control . Technology was carried out at the Massachusetts Institute of Technology (MIT) in cooperation with the company John Parsons Aircraft Corporation in Michigan, USA. This is due to the urgent need to produce very precise parts for complex geometric shapes that form parts of warplanes, especially helicopters. The research problem lies in the fact that the CNC machine is designed to work on drawing only. The CNC is invading the world, so it was necessary to know the methods and theories of its work and how to design a CNC machine from the available local materials at the lowest possible cost. The aim of the research is to design and implement a CNC machine capable of working accurately and at high speed to increase production efficiency, in addition to comparing it with the rest of the machines and observing its performance. The method was used Experimental design and implementation of a CNC machine and compare it with known machines in design materials in terms of cost, and the Arduino C language was used to edit the Arduino program for programming Gil according to modern systems.